PERANAN BADAN PENGAWAS PEMILU (BAWASLU) KABUPATEN LAMONGAN DALAM PENGAWASAN PENYELENGGARA PILKADA SERENTAK DI KABUPATEN LAMONGAN: Studi Terhadap Pemilihan Bupati dan Wakil Bupati Lamongan 2020 - M. Ali Fikri (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
The election of Regional Heads and Deputy Regional Heads is a means of implementing general sovereignty in the Province or Regency/City area based on Pencasila and the 1945 Constitution of the Republic of Indonesia. In the process of holding the 2021 Pilkada in Lamongan Regency, many violations of electoral, administrative and criminal acts were still found. code of Ethics. Violations that occurred during the 2020 regional elections for Regent and Deputy Regent in the 2020 regional elections in Lamongan. This research is included in legal research with a juridical-empirical approach method. The subjects of this research were the chairman of Bawaslu, members of Bawaslu for Lamongan Regency and the Coordinator of the Enforcement and Dispute Resolution Division. Primary and secondary data sources accompanied by primary and secondary legal materials. Data analysis is descriptive-qualitative. Data collection techniques are based on literature studies and field data. The findings in this research are: (i) in following up on violations by Bawaslu, Lamongan Regency, they found 40 cases of suspected violations, including 31 findings and 9 reports. Of the many criminal violations of elections, administration, codes of ethics and other legal violations that were declared or not constituted as violations by Bawaslu of Lamongan Regency because they did not fulfill the material requirements of criminal acts (ii) the violations found in the 2020 Election of Regent and Deputy Regent of Lamongan Regency everything can be resolved well. Keywords: Democracy, Pilkada, Bawaslu